Impact of the use of nano-fertilizers in soybean crop - Ciacci, María Belén; Giachero, María Lorena; Guzzo, María Carla; Imhoff, Silvia; Rosa, Márcio; Guerra da Silva, Alessandro (Sociedade Brasileira de Fisiologia Vegetal (SBFV), 2022)
Poster